A TAKHRIJ AL HADIS DALAM PERSPEKTIF ONTOLOGI DAN AKSIOLOGI ILMU HADIS - zavira orcana; Syahrotun Navisyah; Ida Rochmawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
ABSTRACT The study of hadith is a very important (urgent) science because it is one of the most important sources of Islamic teachings. Apart from the sanad, the study of matan is no less important, and because of its centrality, the study of hadith is important. It involves the study and understanding of hadith and its various aspects and themes. When reading hadith, it is not enough just to refer to dictionaries and hadith books. This is because the hadiths have been collected in many hadith books. Later, takhrîj al-hadîth emerged as a method of tracing hadith back to its original source. And it is developed and connected with the developing philosophical sciences. Among them are the theories of ontology and axciology. As a scientific discourse, the study of this hadith requires the right form and method of research. The author tries to explore how ontologically and axiology athe concept of hadith research